PROCESSES OF EXCLUSION OF PEASANTS AND SMALLHOLDER FARMERS: A SHORT EXPLORATORY STUDY OF TWO CASES IN PORTUGAL AND ANGOLA - Larcher Carvalho, A.; Schiefer, U. (2016)
Peasant and smallholders suffer from exclusion from mainstream economies, policies, and development models. In the industrialised North they have already be reduced to small minorities in many countries exposed to multiple factors (economic, regulatory, administrative, demographic, etc.) that challenge their existence. The Portuguese case study looks into the situation of rural smallholders that face multiple obstacles but still cling on to their existence. Their economic, social and environmental roles have been recognised and recent policies target them, but there has not been enough follow up at local level. As a result, the pressures they face continue to increase, their revenues erode and their livelihoods shrink. There are growing calls to position family farmers at the centre of policies to promote change towards more equitable development. The Angolan case study tries to understand the plight of agrarian societies that have suffered decades of low intensity warfare and have been widely neglected by post-war development strategies. It questions the assumptions of current development strategies, both national and international, for wartorn agrarian societies that have been running for too long on their emergency coping strategies.